2012
DOI: 10.1159/000341222
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Adaptation Capacity of <b><i>Staphylococcus aureus</i></b> to Commonly Used Antiseptics by Microplate Laser Nephelometry

Abstract: Background: Bacterial colonization and infection are important factors in compromised wound healing. Antiseptics have become an alternative for antimicrobial applications as antibiotic resistance is increasing; they have multiple targets with a broad spectrum of activity. Hence, the risk for developing resistance should be low. However, concerns have been raised that their growing use may result in bacteria that are less susceptible. Methods: The capacity of common antiseptics such as silver nitrate, polihexan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 69 publications
0
20
0
Order By: Relevance
“…Furthermore, PVP-iodine shows high bactericidal activity against resistant bacteria strains, e.g. MRSA or Enterococcus faecium [33] and it was shown that it does not induce adaptation in bacteria [34,35]. Yet, its application in wound treatment remains controversial as it may have potential systemic side effects and exert possible cytotoxic effects leading to impaired wound healing [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PVP-iodine shows high bactericidal activity against resistant bacteria strains, e.g. MRSA or Enterococcus faecium [33] and it was shown that it does not induce adaptation in bacteria [34,35]. Yet, its application in wound treatment remains controversial as it may have potential systemic side effects and exert possible cytotoxic effects leading to impaired wound healing [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…However, negative effects on cells of both silver ions21,27 and chitosan formulations22,28,29 have been observed in vitro. Moreover, the use of silver compounds has been associated with the risk of inducing bacterial adaptation 3032. Hence, there is a demand for alternative effective compounds.…”
Section: Discussionmentioning
confidence: 99%
“…photometry [6,12]. Alifax automated nephelometric microbiological analyzers carry out a rapid microbiological analysis within just several hours, including rapid screening of urine for contamination [4,7].…”
mentioning
confidence: 99%